Research on the influence of the cutting speed on the specific cutting force during turning - Velchev, Stefan (Strojniški vestnik, 2009)
A hypothetical graphical dependence showing the cutting speed influence on the specific cutting force when cutting ductile materials is proposed on the basis of the physical nature. Some hypothetical mathematical models for the approximation of that dependence when changing the cutting speed are shown. Trough experimental study when turning different kinds of processed material and mathematical modelling of the experimental data, new mathematical models approximating the dependence of the specific cutting force and cutting speed have been received. A new, better empiric mathematical model when referred to the structure, adequacy and accuracy is recommended.
Keywords: struženje; rezanje; rezalna hitrost; rezalna sila